CSIR the motivational role of interactive control in the research sector: a case study - Kurt Sartorius; Neil Trollip; Carolyn Eitzen; Enrico Uliana (South African Journal of Economic and Management Sciences, 2011)
Performance measurement in the public research sector is complex because of the need to configure stakeholder expectations with operational efficiency. The paper investigates the appropriateness of a performance measurement framework (PMF) in a state controlled research organization in South Africa. A case study method, combined with a survey, is used to test the research questions. The results indicate that the public sector PMF incorporated a checklist of critical success factors, it was sustainable and performance measures had been developed for all the stakeholders. Furthermore, the results indicated that the PMF had facilitated the achievement of the division’s strategic objectives, as well as ancillary objectives like motivation, learning and decision making at a local operations level. Finally, the results suggest that it may be possible to create a generic form of public sector research PMF that is based on the balanced scorecard.